Potential of Staphylea holocarpa Wood for Renewable Bioenergy - Yiyang Li; Erdong Liu; Haiping Gu; Junwei Lou; Yafeng Yang; Longhai Ban; Wanxi Peng; Shengbo Ge (Molecules, 2022)
Energy is indispensable in human life and social development, but this has led to an overconsumption of non-renewable energy. Sustainable energy is needed to maintain the global energy balance. Lignocellulose from agriculture or forestry is often discarded or directly incinerated. It is abundantly available to be discovered and studied as a biomass energy source. Therefore, this research uses Staphylea holocarpa wood as feedstock to evaluate its potential as energy source. We characterized Staphylea holocarpa wood by utilizing FT–IR, GC–MS, TGA, Py/GC–MS and NMR. The results showed that Staphylea holocarpa wood contained a large amount of oxygenated volatiles, indicating that it has the ability to act as biomass energy sources which can achieve green chemistry and sustainable development.